The Relationship Between Social Support From Family and Quality of Life Among Cancer Patients: A Cross-Sectional Study - Ismail Toygar; Öznur Usta Yeşilbalkan; Merve Kürkütlü; Tuğba Akgün (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Improving the Quality of Life (QoL) is considered one of the main objectives in the care of cancer patients. Achieving this objective, it is essential to determine the factors affecting QoL in cancer patients. The studies in the literature have determined the effects of various factors on QoL but social support from family has remained to be studied. Objective: The present study aimed to determine the relationship between perceived social support from family and QoL in cancer patients. Materials and Methods: This cross-sectional study was conducted in an oncology unit of a university hospital in İzmir City, Turkey, from March to October 2019. A convenience sample of 276 cancer patients participated in the study. A patient identification form, the Perceived Social Support from family scale (PSS-Family), and the Quality of Life index-cancer version (QLI-C) were used for data collection. The scores of PSS-Family and QLI-C range from 0 to 20 and from 66 to 396, respectively. Regression analysis was used to estimate the effect of perceived social support from family on QoL. Results: Of the participants, 65.2% were female. The Mean±SD age of the study sample was 47.5±14.4 years. Also, the Mean±SD scores of PSS-Family and QLI-C were 16.43±3.01 and 307.77±27.48, respectively. Regression analysis revealed that perceived social support from family was associated with a relative increase in QoL index (B=3.44, P=0.001, R2=0.141). Conclusion: Perceived social support from family is positively associated with QoL in cancer patients. Nurses should consider this relationship when they plan to improve the QoL of cancer patients.